Edukasi Potensi Sumber Daya Ikan untuk Meningkatkan Pengetahuan Gizi dan Imunitas Anak di SMP Negeri 6 Maluku Tengah - Meillisa Carlen Mainassy; Deford Christy Birahy (Universitas Sebelas Maret, 2023)
Adequate nutrition is needed by every individual, including school-age children. The aim of this activity is to provide education on the potential of fish resources to increase children's nutritional knowledge and immunity. The method used is lecture and discussion with a participatory approach. The material is given in the form of presentations or lectures, as well as watching videos about the benefits of consuming fish and its processed products. This activity was carried out at SMP Negeri 6 Maluku Tengah, Haruku Island, Central Maluku Regency. The result of implementing the activity is that children have insight and knowledge of fish processing models, nutritional value in increasing immunity. The evaluation results based on the post test show that the source of fish for consumption is 60% of the catch, 100% of the fish obtained is fresh, and the reason for consuming fish is to improve health by 45%, and the traditional processing model is 89% in the form of yellow sauce fish dishes 44%.